Pathological Characteristics of Primary Bladder Carcinoma Treated at a Tertiary Care Hospital and Changing Demographics of Bladder Cancer in Sri Lanka - S. Sasikumar; K. S. N. Wijayarathna; K. A. M. S. Karunaratne; U. Gobi; A. Pathmeswaran; Anuruddha M. Abeygunasekera (Advances in Urology)
Objectives. The aim was to compare demographics and pathological features of bladder carcinoma treated in a urology unit with findings of previous studies done in Sri Lanka. Materials and Methods. Data of newly diagnosed patients with bladder cancer in a tertiary referral centre from 2011 to 2014 were analysed. Data on bladder cancers diagnosed from 1993 to 2014 were obtained from previous publications and Sri Lanka Cancer Registry. Results. There were 148 patients and mean age was 65 years. Male to female ratio was 4.1 : 1. Urothelial carcinoma (UC) was found in 89.2% of patients. Muscle invasion was noted in 35% of patients compared to 48.4% two decades ago. In patients with UC, 16.5% were found to have pT1 high grade tumour. It was 5.3% from 1993 to 2000. Pure squamous cell carcinoma was found in 8.1% of patients while primary or de novo carcinoma in situ (not associated with high grade pT1 tumours) was seen in one patient only. Conclusions. The percentage of squamous carcinoma is higher among Sri Lankan patients while primary carcinoma in situ is a rarity. The percentage of muscle invasive disease has decreased while the percentage of pT1 high grade tumours has increased during the last two decades in Sri Lanka.